A Comparative Histopathology, Serology and Molecular Study, on Experimental Ocular Toxocariasis by Toxocara cati in Mongolian Gerbils and Wistar Rats. (29th August 2013) - Zibaei, Mohammad; Sadjjadi, Seyed Mahmoud; Karamian, Mehdi; Uga, Shoji; Oryan, Ahmad; Jahadi-Hosseini, Seyed Hamidreza
Abstract : The aim of this study was to compare the performance of three in-house diagnostic tests, that is, histopathology, enzyme-linked immunosorbent assay (ELISA), and polymerase chain reaction (PCR), for the diagnosis after experimental infection with Toxocara cati . Twenty Mongolian gerbils and Wistar rats were divided into ten groups (n = 2 /group). Toxocara cati infections were established in Mongolian gerbils and Wistar rats by administering doses of 240 and 2500 embryonated Toxocara cati eggs by gavage, respectively. Tissue sections were stained with Haematoxylin and Eosin and observed under the light microscope. Sera and vitreous fluid collected from separate infected groups were tested against Toxocara cati antigens, for 92 days postinfection. Genomic DNA was extracted from formalin-fixed paraffin-embedded (FFPE) blocks, and aqueous fluids belong to the animals. The histopathology test gave negative results among the groups of animals examined between 5 and 92 days postinfection. The ELISA results showed that anti- Toxocara antibodies have risen between 7 and 61 days postinfection in sera and vitreous fluid in the animals infected, respectively. Analysis of PCR products revealed positive band (660 bp) in the orbital tissue infected Mongolian gerbils at 5 days postinfection. Of the three evaluated methods, the PCR could be recommended for scientific and laboratory diagnoses of toxocariasis in experimentally infected animals.